Caracterização do habitat e aspectos ecológicos de Anisotremus moricandi (Perciformes: Haemulidae) em dois ambientes recifais costeiros da Paraíba, Brasil - Araújo, Antônio Limeira Felinto de (2016)
The species Anisotremus moricandi is distributed along the coast of Northeast Brazil and occurs in reef environments near the coast, suffering some human impacts from recreational activities, fishing and pollution. Currently, according to the IUCN (2015), the species is listed in the category “Least Concern” (LC), but despite this position, knowledge about its biology, ecology and fishing is still incipient, which creates great concern about the conservation status of this species. In this sense, this study aimed to characterize the populations and the habitat of A. moricandi on coastal reefs of Cabo Branco e Seixas, which are located in João Pessoa, Paraíba. Samples were collected during the summer period of 2014 and 2015. The abundance and habitat of this species were assessed through daytime snorkeling dives by using linear transects. 60 censuses were conducted (30/site), totaling 227 records of A. moricandi, with a greater number of juvenile individuals, mainly in Cabo Branco reefs. The microhabitat most used by A. moricandi was “reef crevice”, where individuals were seen in most census resting in these structures. The species occur predominantly in areas with rocks. The abundance of A. moricandi was positively related to the amount of reef crevices where juvenile fish use these structures as protection sites. Compared to other studies, it is observed that in Cabo Branco and Seixas reefs there was a greater record of this species, so it can be inferred that these environments have key resources for the survival of A. moricandi. However, it is necessary to preserve these areas in order to maintain that species, as A. moricandi occurs on reefs near shore and is quite vulnerable to human activities.